2014
DOI: 10.1016/s1470-2045(14)70361-4
|View full text |Cite|
|
Sign up to set email alerts
|

Active monitoring, radical prostatectomy, or radiotherapy for localised prostate cancer: study design and diagnostic and baseline results of the ProtecT randomised phase 3 trial

Abstract: UK National Institute for Health Research Health Technology Assessment Programme.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
191
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 208 publications
(198 citation statements)
references
References 35 publications
5
191
0
2
Order By: Relevance
“…This trial is a primary-care based cluster-randomized trial of a single PSA test, 14 within which the ProtecT trial of treatments for localized prostate cancer was embedded 15 (Supplementary Figure S1). Between 2001 and 2009, 785 eligible general practices around 8 hospital centers in England and Wales were randomized before recruitment ('Zelen' design) to intervention-or control-groups and approached for consent to participate.…”
Section: Randomizationmentioning
confidence: 99%
“…This trial is a primary-care based cluster-randomized trial of a single PSA test, 14 within which the ProtecT trial of treatments for localized prostate cancer was embedded 15 (Supplementary Figure S1). Between 2001 and 2009, 785 eligible general practices around 8 hospital centers in England and Wales were randomized before recruitment ('Zelen' design) to intervention-or control-groups and approached for consent to participate.…”
Section: Randomizationmentioning
confidence: 99%
“…These challenges are very likely to be encountered in a RCT comparing focal therapy to a standard option in light of the different toxicity profiles of the two arms, as well as the debate surrounding the legitimacy of focal therapy among clinicians. If such trial would be revealed unfeasible, an alternative way of randomization should be explored -such as what the researchers have applied within the ProtecT trial -or alternative trial designs should be considered in order to evaluate in a rigorous and timely manner a focal therapy option (51). Cancer control in studies with intention to treat is encouraging, although this needs to be verified against standard of care in high quality comparative effectiveness trials.…”
Section: Brachytherapymentioning
confidence: 99%
“…90 An RCT comparing watchful waiting with radical prostatectomy is ongoing in the United Kingdom. 13,91 Taken together, therefore, these data show that benefits from improvements in prostate cancer risk prediction, screening, and prognostic stratification will depend to a large extent on clearer evidence that surveillance, diagnostic, and treatment strategies in themselves lead to reductions in morbidity and mortality.…”
Section: Discussionmentioning
confidence: 97%